FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT KECEMASAN MAHASISWA PROFESI NERS DALAM MENGIKUTI PRAKTIK KLINIK KEPERAWATAN [FACTORS ASSOCIATED WITH THE LEVEL OF ANXIETY OF NURSING STUDENTS IN PARTICIPATING IN NURSING CLINICAL PRACTICE] - Muthia Nufus Fadhilah; Ani Haryani; Yeni Binteriawati; Herna Alifiani (Universitas Pelita Harapan, 2023)
Clinical learning aims to facilitate students in deepening, testing, and applying the concepts of the subject matter in clinical practice. Additionally, clinical learning also aims to develop students' psychomotor, intellectual, and attitude skills in creating care plans for patients. However, during clinical practice, students often experience anxiety, especially when they are in unfamiliar rooms and confronted with demanding patient families who have doubts about the nursing actions performed by the students. The purpose of this study is to identify factors associated with the level of anxiety among professional nursing students in participating in nursing clinical practice at Faletehan University. The research adopts a cross-sectional design methodology. The study population consists of all nursing professional students at Faletehan University, totaling 124 students. A total sampling technique was used, resulting in 124 respondents as the research sample. The results of the univariate analysis indicate that 54.8% of the respondents experience mild anxiety, 55.6% of the respondents have inadequate knowledge, 59.7% of the respondents have supportive family support, and 54.8% of the respondents perceive the hospital environment as unfavorable. The bivariate analysis using chi squared reveals that factors associated with anxiety among professional nursing students are knowledge (P value 0.000), family support (P value 0.000), and the hospital environment (P value 0.000). It is recommended to focus on the factors of knowledge, hospital environment, and family support, as well as to motivate students to enhance their knowledge and the nursing process. This approach is expected to assist students in overcoming anxiety and improving the quality of their clinical practice.BAHASA INDONESIA ABSTRAK Pembelajaran klinik memiliki tujuan untuk mempermudah mahasiswa dalam mendalami, menguji, dan mengaplikasikan konsep materi dalam praktek klinik. Selain itu, pembelajaran klinik juga bertujuan untuk mengembangkan pengetahuan psikomotor, intelektual, dan sikap mahasiswa dalam membuat asuhan kepada pasien. Namun, dalam pelaksanaan praktik klinik, seringkali mahasiswa mengalami kecemasan, terutama saat mereka berada di ruangan yang baru dan dihadapkan dengan keluarga pasien yang rewel serta kurang percaya terhadap tindakan keperawatan yang dilakukan oleh mahasiswa praktik. Tujuan penelitian ini untuk mengetahui faktor-faktor yang berhubungan dengan tingkat kecemasan mahasiswa profesi Ners dalam mengikuti praktik klinik keperawatan di Universitas Faletehan. Penelitian menggunakan metode desain cross sectional. Sampel penelitian ini seluruh mahasisawa Ners berjumlah 124 responden dengan menggunakan teknik total sampling. Hasil analisis univariat menunjukkan bahwa sebanyak 54,8% responden mengalami kecemasan ringan, 55,6% responden memiliki pengetahuan yang kurang baik, 59,7% responden memiliki dukungan keluarga yang mendukung, dan 54,8% responden merasa lingkungan RS kurang baik. Hasil analisis bivariat mengunakan uji chi kuadrat menunjukkan bahwa faktor-faktor yang berhubungan dengan kecemasan mahasiswa profesi Ners adalah pengetahuan (P value 0.000), dukungan keluarga (P value 0.000), dan lingkungan RS (P value 0.000). Diharapkan untuk memfokuskan perhatian terhadap faktor pengetahuan, lingkungan RS, dukungan keluarga, serta memotivasi mahasiswa untuk meningkatkan pengetahuan dan proses tindakan keperawatan. Hal ini diharapkan dapat membantu mahasiswa mengatasi kecemasan dan meningkatkan kualitas praktik klinik.